Bad cops and true detectives: The horror of police and the unthinkable world - Linnemann, Travis (Theoretical criminology, 2019)
The first season of the HBO series True Detective has drawn attention to Eugene Thacker's horror of philosophy trilogy and his tripartite mode of thinking of the world and the subject's relation to it. This article is an effort to read Thacker's speculative realism into a critique of the police power. Where the police concept is vital to sustaining the Cartesian world-for-us, a world of mass-consumption and brutal privation, the limitations, failures or absence of police might also reveal horizons of disorder—primitivism, anarchism—the world-in-itself. A critical reading of True Detective and other police stories suggests that even its most violent and corrupt forms, as inseparable from security, law and order, the police power is never beyond redemption. What is rendered unthinkable then is the third ontological position—a world-without-police—as it exposes the frailties of the present social order and the challenges of thinking outside the subject.